2014
DOI: 10.1111/sum.12148
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics in wheel load‐carrying capacity of a loam soil in the Swiss Plateau

Abstract: Subsoil compaction is a major problem in modern agriculture caused by the intensification of agricultural production and the increase in weight of agricultural machinery. Compaction in the subsoil is highly persistent and leads to deterioration of soil functions. Wheel load‐carrying capacity (WLCC) is defined as the maximum wheel load for a specific tyre and inflation pressure that does not result in soil stress in excess of soil strength. The soil strength and hence WLCC is strongly influenced by soil matric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Associated bulk density values up to 1.51 g cm −3 were observed for a loamy soil under vineyard and orchard land uses subjected to vehicle traffic [11]. In a loam soil of the Swiss Plateau, tilled with a direct drilling, Gut et al [41] found an average BD value of 1.47 g cm −3 at depth 0.1-0.16 m. In an investigation conducted by Boydell and Boydell [42] in Vertisols used for grain cropping, machinery traffic determined bulk densities in the range 1.25-1.45 g cm −3 at depth of 0.05-0.5 m. In a sandy loam soil, machinery traffic applied when the soil was dry (mean soil moisture 0.066 g g −1 ) resulted in an average BD = 1.59 g cm −3 at 0.15 to 0.30 depth [43]. Although care was put to avoid the wheel tracks during sampling, these results also indicate that Les Alcusses soil was throughout compacted by machinery operations due to the pass of lorries, vans, tractors, and men at the time of vineyard establishment.…”
Section: Discussionmentioning
confidence: 97%
“…Associated bulk density values up to 1.51 g cm −3 were observed for a loamy soil under vineyard and orchard land uses subjected to vehicle traffic [11]. In a loam soil of the Swiss Plateau, tilled with a direct drilling, Gut et al [41] found an average BD value of 1.47 g cm −3 at depth 0.1-0.16 m. In an investigation conducted by Boydell and Boydell [42] in Vertisols used for grain cropping, machinery traffic determined bulk densities in the range 1.25-1.45 g cm −3 at depth of 0.05-0.5 m. In a sandy loam soil, machinery traffic applied when the soil was dry (mean soil moisture 0.066 g g −1 ) resulted in an average BD = 1.59 g cm −3 at 0.15 to 0.30 depth [43]. Although care was put to avoid the wheel tracks during sampling, these results also indicate that Les Alcusses soil was throughout compacted by machinery operations due to the pass of lorries, vans, tractors, and men at the time of vineyard establishment.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the soil may be more prone to slaking and subsequent surface sealing in MP due to soil destabilisation during fragmentation by tillage, which could drastically reduce soil aeration even under dry conditions (Håkansson et al, 2012). Gut et al (2015) reported no difference in the long-term average soil matric potential at 0.3 m depth between NT and MP. However, Chervet et al (2006) found on average slightly more moist conditions in NT than in MP in maize during the summer months (June to August) based on tensiometer and TDR measurements during the period 1998-2005.…”
Section: Soil Aeration and Implications For Plant Growthmentioning
confidence: 99%
“…Table A2). In the decision matrix of Lorenz et al [22], the compaction risk is assessed by combining the susceptibility of soils to compaction and the mechanical load applied by machinery, as commonly used in soil compaction risk assessment [2,32,37,47,48] (Figure 3). Thresholds for each soil type to divide them into five susceptibility classes have been defined by an expert consortium (Appendix B, Figure A1).…”
Section: Machinery Datamentioning
confidence: 99%
“…The use of heavy machinery and intensive field traffic can lead to a soil load that exceeds the intrinsic stability and resilience of soil structure and induces soil compaction. Soil compaction is a worldwide problem in agriculture, but particularly in regions with high mechanization rates in the production chain [1,2] and high precipitation [3]. The process of soil compaction leads to a reduction of pore volume and change in pore structure and negatively influences the gas, water, and nutrient exchanges [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation